Analisis Perencanaan Strategis dan Pengawasan Mutu dalam Lembaga Pendidikan Islam - Muhamad Zikrulloh; Siti Alfiah Yulistiani; Herni Martini; Fariz Fudla Fasih; Ika Kartika (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation, effectiveness, and relevance of Strategic Planning and Quality Control mechanisms in Islamic Educational Institutions (LPI). LPIs are required not only to maintain Islamic traditions but also to adapt to global dynamics and demands for quality service. Sound strategic planning is the foundation for achieving LPI's vision, mission, and long-term goals, while integrated quality control ensures the sustainable achievement of quality standards. The results show that the integration of Islamic values, such as amanah (trust), ihsan (goodness), and deliberation (musyawarah) in every stage of management is crucial for achieving Total Quality Education (TQE) that is oriented towards both the worldly and the hereafter.